Comparison of turmeric extract (Curcuma longa) with red ginger (Zingiber officinale Linn. Var. rubrum) in inhibiting the growth of Streptococcus mutans in vitro: Perbandingan ekstrak kunyit (Curcuma longa) dengan jahe merah (Zingiber officinale Linn. Var. rubrum) dalam menghambat pertumbuhan Streptococcus mutans in vitro - Dwis Syahrul; Haris Nasutianto; Gabriel Natanael Hutabarat (Makassar Dental Journal PDGI Makassar, 2023)
The long-term use of 0.2% chlorhexidine (CHX) to inhibit the growth of Streptococcus mutans is detrimental so that alterna-tives are needed, including turmeric and red ginger; both contain antibacterial. This study aims to compare the inhibition of turmeric extract with red ginger against S.mutans in vitro. Inhibition test with agar disk diffusion method and nutrient agar (NA) culture media. Turmeric and red ginger extract 15%, 30%, 60%, control (+) CHX 0.2%, control (-) aquadest. One-way Anova test extracts of turmeric and red ginger were significantly different (p<0.05). The LSD test of turmeric or red ginger extract 15%, 30%, 60% was significantly different from aquadest. Both 60% extracts have the same value (0.098) not signifi-cantly different from CHX. T-test of 60% extract between the two (1.00) was not significantly different (p>0.05). Extracts of turmeric and red ginger 15%, 30%, 60% are able to inhibit S.mutans compared to aquadest. Extracts of 60% turmeric and red ginger were not significantly different from CHX. Both 60% extracts were not significantly different. It is concluded that tur-meric and red ginger extracts 15%, 30%, 60% were able to inhibit S.mutans, and both 60% extracts were not significantly dif-ferent, but had similar efficacy to CHX in vitro.